Perancangan Alat Pengupas Buah Durian Di UKM Pancake Lena - Yenny Chandra; Dominikus Budiyarto (Universitas Katolik Musi Charitas, 2017)
Pancake Lena is the small and medium industries that produce durian pancake. These SMEs durian pancake producing as many as 600 pieces per day. For the manufacture of pancakes per day SMBs can spend as much as 25 durian fruit. Preliminary observations on the initial durian peel using a knife, but by using this way many factors that cause accidents and long lead time process. The average time for the start of durian peel 1.1 minutes while peeling durian total with an average time of 3.3 minutes. In the observations were made for 25 pieces of durian with a work accident as much as 4 times. To solve the problem time and productivity happens to need a durian peeler. How it works peeler durian by sticking a durian on a crutch durian, then there are two claws blade left and right to stab the left side and the upper right durian, then the driver is struck so that the claw knife stab to the durian, and the left stick and right-drawn simultaneously to open a durian. The design of this durian peeler using R&D (Research and Development), which is a method of research and product development. The tool development considersefficiency, product effectivity and ease of useof product design. The efficiency of stripping time early durian fruit on average 0.11 minutes while peeling fruit durian total with an average time of 1.02 minutes and accidents reduced and productivity before and after obtained a 2,22 earned 2,27. Specifications tool designed measuring 50 cm long and 92 cm high.